Influence of Twinning Microstructure of Crystals with Low Tetragonality on a X-Ray Diffraction - A. I. Ustinov (Успехи физики металлов, 2001)
The intensity distributions of the X-rays scattered in the tetragonal single crystal, which represent a complex of the twin domains separated by the coherent parallel boundaries, are simulated. The calculations are performed by using the Monte Carlo method within the framework of a kinematical approach. The thickness distributions of the twin domains are defined according to the geometrical, Gaussian and log normal functions. ‘Critical’ effects of the X-ray scattering are found, namely there is transformation of the tetragonal doublet into singlet or multiplet. As demonstrated, each of characteristics of the tetragonal doublet profile depends on a few parameters of the twin microstructure of a crystal and cell tetragonality as well.